2019
DOI: 10.1371/journal.pone.0221570
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tolerance of industrial hemp (Cannabis sativa L.) plants on abandoned mine land soil leads to overexpression of cannabinoids

Abstract: Industrial activities have a detrimental impact on the environment and health when high concentrations of pollutants are released. Phytoremediation is a natural method of utilizing plants to remove contaminants from the soil. The goal of this study was to investigate the ability of Cannabis sativa L. to sustainably grow and remediate abandoned coal mine land soils in Pennsylvania. In this study, six different varieties of industrial hemp (Fedora 17, Felina 32, Ferimon, Futura 75, Santhic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 38 publications
2
30
3
2
Order By: Relevance
“…Since phytoremediation is influenced by cultivar selection and plant genetics (Adamovičs et al, 2014;Mihoc et al, 2012;Petrová et al, 2012;Shi et al, 2012), the legal limitation of hemp based on low THC content dramatically reduces the number of C. sativa varieties that can be investigated for combined phytoremediation and bioenergy production. Furthermore, research has indicated that cannabinoids are overexpressed as a result of heavy metal accumulation (Husain et al, 2019), which has the potential to exacerbate legality issues when hemp is used for phytoremediation. This area might be expanded with special policy exceptions, such as those granted to hemp breeders for variety development, to F I G U R E 1 Flow chart for production of bioenergy from hemp, adapted from process diagrams described in Kreuger, Prade, et al (2011) Maximal 137 Cs soil contamination levels calculated using the lower value for the decontamination factor listed.…”
Section: Phytoremediation and Bioenergy Productionmentioning
confidence: 99%
“…Since phytoremediation is influenced by cultivar selection and plant genetics (Adamovičs et al, 2014;Mihoc et al, 2012;Petrová et al, 2012;Shi et al, 2012), the legal limitation of hemp based on low THC content dramatically reduces the number of C. sativa varieties that can be investigated for combined phytoremediation and bioenergy production. Furthermore, research has indicated that cannabinoids are overexpressed as a result of heavy metal accumulation (Husain et al, 2019), which has the potential to exacerbate legality issues when hemp is used for phytoremediation. This area might be expanded with special policy exceptions, such as those granted to hemp breeders for variety development, to F I G U R E 1 Flow chart for production of bioenergy from hemp, adapted from process diagrams described in Kreuger, Prade, et al (2011) Maximal 137 Cs soil contamination levels calculated using the lower value for the decontamination factor listed.…”
Section: Phytoremediation and Bioenergy Productionmentioning
confidence: 99%
“…Systematic identification of the whole hemp genome and related research into Cd stress is necessary. In recent years, studies have found that exogenous heavy metal stress can increase CBD, a representative cannabinoid, content in hemp [19]. One of the objectives of this study was to determine whether Cd stress leads to changes in the content of cannabinoids by affecting the expression of MYB genes.…”
Section: Introductionmentioning
confidence: 99%
“…These transcription factors are targets to activate cannabinoid synthesis. Notably, cannabinoid synthesis is expedited by UV light application or heavy metal ( Zhang and Björn, 2009 ; Husain et al, 2019 ). The elucidation of signal transduction triggered by these elicitors may lead to the discovery of positive and negative regulators of signal transduction, which will be the target genes for hemp metabolic engineering.…”
Section: Strategies Of Target Gene Selection For Enhancing Phytochemimentioning
confidence: 99%